2022
DOI: 10.1200/jco.2022.40.6_suppl.556
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and clinical outcomes of HER2-altered bladder cancer (BC) patients (pts).

Abstract: 556 Background: Bladder cancer has one of the highest rates of human epidermal growth factor receptor 2 (HER2) alteration. Novel HER2-directed agents are being investigated in metastatic BC. We sought to define the incidence and clinical characteristics of HER2-altered BC across disease states. Methods: We retrospectively analyzed our single-institution, clinically annotated cohort of urothelial BC pts with available genomic profiling data (MSK-IMPACT). We quantified the prevalence of HER2 alterations, define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…One trial (NCT03740256) combines the use of a human epidermal growth factor receptor 2 (HER2)–specific CAR T with an immunostimulatory oncolytic virus to enhance immune reactivity. HER2 has been found to be altered in bladder cancer and in a study was found to be altered in 16% of bladder tumors 62,63 . Overall, CAR T cells for the treatment of bladder cancer are in the early stages of clinical development and target antigens that are overexpressed in bladder tumors.…”
Section: Act In Bladder Cancermentioning
confidence: 97%
See 1 more Smart Citation
“…One trial (NCT03740256) combines the use of a human epidermal growth factor receptor 2 (HER2)–specific CAR T with an immunostimulatory oncolytic virus to enhance immune reactivity. HER2 has been found to be altered in bladder cancer and in a study was found to be altered in 16% of bladder tumors 62,63 . Overall, CAR T cells for the treatment of bladder cancer are in the early stages of clinical development and target antigens that are overexpressed in bladder tumors.…”
Section: Act In Bladder Cancermentioning
confidence: 97%
“…HER2 has been found to be altered in bladder cancer and in a study was found to be altered in 16% of bladder tumors. 62,63 Overall, CAR T cells for the treatment of bladder cancer are in the early stages of clinical development and target antigens that are overexpressed in bladder tumors.…”
Section: Car T Cellsmentioning
confidence: 99%
“…HER2 is overexpressed in 12.4% of UC [65,70]. Moreover, potentially targetable HER2 mutations in UC may be underrecognized with a prevalence of 11% and are enriched in tumors with micropapillary histology [71][72][73]. Despite considerable interest in HER2 as a target in UC, trials involving kinase inhibitors, monoclonal antibodies, and even the ADC trastuzumab emtansine (T-DM1) have generated underwhelming efficacy results or concerning toxicity profiles [74,75].…”
Section: Her2 Adcs In Bladder Cancermentioning
confidence: 99%
“… 9 In addition, HER2 amplification is enriched in muscle invasive bladder cancer (MIBC) and metastatic disease compared with non-muscle invasive bladder cancer (NMIBC). 10 Therefore, HER2 alteration might be correlated with aggressive disease in bladder cancer.…”
Section: Introductionmentioning
confidence: 99%